How do titanium and Ti6A14V corrode in fluoridated medium as found in the oral cavity? an in vitro study - Souza, Julio C. M.; Barbosa, Sandra L.; Ariza, Edith A.; Henriques, Mariana; Teughels, Wim; Ponthiaux, Pierre; Celis, Jean-Pierre; Rocha, Luis A. [UNESP] (Elsevier B.V., 2015)
The purpose of this work was to evaluate the corrosion of commercially pure (CP) titanium and Ti6Al4V in vitro at different F- concentrations regularly found in the oral cavity by using different electrochemical tests and surface analysis techniques. electrochemical impedance spectroscopy (EIS), open circuit potential (OCP) and potentio-dynamic polarization tests were associated to advanced characterization techniques such as SEM, EDS, AFM, ICP-MS and XPS. OCP tests revealed a higher reactivity of both CP titanium and Ti6Al4V at 12,300 ppm F- concentration than that recorded at 227 ppm F-. Also, a significant decrease of the corrosion resistance of both materials was noticed by EIS in fluoride solutions. Material loss caused by corrosion was noticed on titanium surfaces by SEM and AFM in the presence of high F- concentration. CP titanium degraded by pitting corrosion while Ti6Al4V suffered from general corrosion showing micro-cracks on surface. Furthermore, a high release of metallic ions from the test samples after immersion at high F concentrations was detected by ICP-MS, that can be potentially toxic to oral tissues. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Titanium; Fluoride; Ti6Al4V; Electrochemical tests; Surface analysis